2016
DOI: 10.1109/jphot.2016.2552820
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Distributed Vibration Sensing Based on Phase Extraction From Phase-Sensitive OTDR

Abstract: Distributed fiber-optic vibration sensors based on phase-sensitive optical timedomain reflectometry (-OTDR) have found many applications in various fields. In this paper, we analyze the phase noise of -OTDR, which is the main limiting factor of the measurement range. We found that the laser phase noise and phase extraction error caused by the intensity noise in photodetection contribute to the total phase noise. By introducing a series of auxiliary weak reflection points along the fiber, we develop a phase-noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…This technique was validated by Tu et al (Tu 2015) and later by Yang et al (Yang 2016). The experimental results published by Yang et al showed that this sensing technique is capable of spatially resolving 1kHz dynamic strains along 30km of sensing fibre with a spatial and strain resolution of 10m and 50nε, respectively.…”
Section: C) Electrical-domain Techniquementioning
confidence: 90%
“…This technique was validated by Tu et al (Tu 2015) and later by Yang et al (Yang 2016). The experimental results published by Yang et al showed that this sensing technique is capable of spatially resolving 1kHz dynamic strains along 30km of sensing fibre with a spatial and strain resolution of 10m and 50nε, respectively.…”
Section: C) Electrical-domain Techniquementioning
confidence: 90%
“…X. Fan et al have demodulated the phase information successfully by Hilbert transform, and deeply studied the noise of phase [18][19]. F. Pang et al have obtained the spatial distribution characteristic of the statistical phase in the coherent Φ-OTDR system when the phase demodulation is used to resolve the fading discrimination [20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, precisely demodulating the phase of the reflected lightwave is the key to solve for the distributed perturbation along an optical fiber. A number of demodulation methods have been proposed in the past [12][13][14][15][16][17]. A. Masoudi and M. Belal used a 3×3 coupler to measure multiple dynamic perturbations along a 1 km fiber [16].…”
Section: Introductionmentioning
confidence: 99%
“…Y. Dong proposed a quantitative measurement system using I/Q demodulation method [13]. G. Yang developed a vibration sensing technique based on Φ-OTDR using Hilbert transform, which is able to measure dynamic strain at a frequency as low as 30 Hz [14].…”
Section: Introductionmentioning
confidence: 99%